THE ROLE OF MONETARY POLICY DALAM PEREKONOMIAN DI INDONESIA - Putri, Agustina Irwani; Febriyanti, Putri; Astuti, Yulia; Akbar, M. Faiz (STAI Darul Qalam Tangerang, 2024)
This research is to find out about the role of monetary policy in the economy in Indonesia. Economic growth is an illustration of the impact of government virtues carried out, especially in the economic sector. The challenges faced by the financial industry include solving the problem of form above substance, dealing with value-based social finance and ethics, and strengthening public trust. These challenges can only be faced if finance is based on an economic monetary perspective. Monetary policy aims to achieve and maintain rupiah stability. The method of writing this scientific journal is by qualitative method and literature study or library research. Examine and study literature books in accordance with the theories discussed, especially in the scope of the concept of the role of monetary policy in the economy. In qualitative research, literature review should be used consistently with methodological assumptions